ANALISIS KEPUASAN PELANGGAN INTERNAL TERHADAP PENCAPAIAN STANDAR PROSES PEMBELAJARAN POLTEKKES KEMENKES SEMARANG - Hermien Nugraheni; Lanny Sunarjo; Enik Sulistyowati (Jurnal Kesehatan Gigi, 2017)
TITLEINTERNAL CUSTOMERS SATISFACTION ANALYSIS TOWARD ACHIEVEMENT OF EDUCATION PROCESS STANDARD IN POLTEKKES KEMENKES SEMARANGABSTRACTIn the cycle of continuous quality improvement, standards need to be evaluated and improved through benchmarking on an ongoing basis. National Standards for Higher Education (SNPT) is set to develop a service quality educational unit. The purpose of this study is to analyze the internal customer satisfaction towards the achievement of the learning process standards in the Ministry of Health Polytechnic Semarang.This study uses a descriptive-quantitative method with performance Importance and Performance Analysis / Customer Satisfaction. Research carried out by the academic community population that consists of elements: students, lecturers, and employees (internal). It affects the variable is Internal Customer Satisfaction and variable influence is the quality of services that include attributes: reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy), and tangible (physical evidence).As a result, for Student customers, which should be improved in the future, namely: ease of connection, physical infrastructure, and customer cost. For Lecturers, which should be improved in the future, namely: ease of intercourse and Physical Infrastructure. As for customer Employees must be improved in the future, namely: ease of intercourse and Physical Infrastructure. Users have the perception of the graduates of polytechnic graduates performance MoH Semarang with the assessment that the integrity, professionalism, ability to communicate in English, ability uses of Information Technology, Interact capability, Teamwork, and Personal Development in both categories. Keywords : Satisfaction, Customer, Learning Process